The evolution of land plant cilia - Hodges, M; Wickstead, B; Gull, K; Langdale, J (2012)
Eukaryotic cilia/flagella are ancient organelles with motility and sensory functions. Cilia display significant ultrastructural conservation where present across the eukaryotic phylogeny; however, diversity in ciliary biology exists and the ability to produce cilia has been lost independently on a number of occasions. Land plants provide an excellent system for the investigation of cilia evolution and loss across a broad phylogeny, because early divergent land plant lineages produce cilia, whereas most seed plants do not. This review highlights the differences in cilia form and function across land plants and discusses how recent advances in genomics are providing novel insights into the evolutionary trajectory of ciliary proteins. We propose a renewed effort to adopt ciliated land plants as models to investigate the mechanisms underpinning complex ciliary processes, such as number control, the coordination of basal body placement and the regulation of beat patterns. © 2012 The Authors. New Phytologist © 2012 New Phytologist Trust.